FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP HARGA DAN RETURN SAHAM PADA PERUSAHAAN PERBANKAN (PERSERO) YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2022 - Desi Nadia Natalia; Erni Setiawati; Firmansyah Firmansyah; Nadya Yunan (OBOR: Oikonomia Borneo, 2024)
The stock price serves as a crucial benchmark for assessing a company's operational quality and prospects. The higher a company's stock price, the better its prospects. Conversely, if a company's stock price is low, it may indicate less promising priorities and prospects. Return on stock is a critical parameter that reflects the difference between the stock's book value and market price. This value indicates the extent of profit a company gains from stock sales transactions. Return on stock is one of the key indicators in evaluating a company's performance and attracting investor interest. This research employs a reliable quantitative method to analyze complex phenomena and produce robust and dependable findings. The selected population consists of four banking companies listed on the Indonesia Stock Exchange during the period from 2017 to 2022, providing broad and relevant data coverage to depict long-term trends. The applied data analysis technique is multiple linear regression analysis, enabling researchers to identify and measure cause-and-effect relationships between relevant variables. The research yields intriguing results, demonstrating that Loan to Deposit Ratio, Return on Asset, and Debt to Equity Ratio have a negative and significant impact on Stock Price. In contrast, Stock Price itself shows a positive and significant influence on stock return. The conclusion of this study offers valuable insights to market participants, investors, and stakeholders associated with the examined banking companies. The analysis outcomes can be used as a foundation for making intelligent and strategic investment decisions, as well as providing profound understanding of the factors influencing a company's stock performance in the capital market. Keywords: Stock Price, Loan to Deposit Ratio, Return on Asset, Debt to Equity Ratio, Stock Return.